2023
DOI: 10.3390/healthcare11182536
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Its Affecting Factors among Hemodialysis Patients: A Multicenter Cross-Sectional Study

Bushra Alshammari,
Sameer A. Alkubati,
Eddieson Pasay-an
et al.

Abstract: (1) Background: Sleep quality is one of the most important clinical outcomes of hemodialysis (HD) patients, as it can affect their physical and mental health. This study aimed to investigate sleep quality and its affecting factors among patients with HD. (2) Methods: A cross-sectional design was used to investigate the quality of sleep among HD patients in two cities in Saudi Arabia. The data were collected during the period from January to December 2022. A convenience sample of 250 HD patients was selected in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
(98 reference statements)
2
2
0
2
Order By: Relevance
“…In our study, the prevalence of poor quality of sleep was found to be 42.9% with 95% CI (38 to 47%), which was similar to the reported prevalence from Turkey (42.2%) (18), but higher than the prevalence observed in two other studies from Saudi Arabia (36.4%) (22), and Japan (37%) (36). Possible reasons for these variations could be attributed to differences in sample sizes, with Saudi Arabia having a smaller sample size, and variations in the assessment tool's cutoff value, such as Japan using a cutoff of ≥6 to evaluate sleep quality.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In our study, the prevalence of poor quality of sleep was found to be 42.9% with 95% CI (38 to 47%), which was similar to the reported prevalence from Turkey (42.2%) (18), but higher than the prevalence observed in two other studies from Saudi Arabia (36.4%) (22), and Japan (37%) (36). Possible reasons for these variations could be attributed to differences in sample sizes, with Saudi Arabia having a smaller sample size, and variations in the assessment tool's cutoff value, such as Japan using a cutoff of ≥6 to evaluate sleep quality.…”
Section: Discussionsupporting
confidence: 86%
“…Another factor associated with poor sleep quality was older age, which was supported by other studies ( 9 , 18 , 22 , 37 , 52 ). Aging is associated with decreased ability to maintain sleep, reduced nocturnal sleep duration, and decreased deep sleep ( 53 ).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Gangguan tidur yang dirasakan oleh pasien dapat menyebabkan penurunan tingkat kelangsungan hidup pada pasien hemodialisis, yang menekankan pentingnya mengatasi masalah tidur pada pasien hemodialisis (Al Naamani et al, 2021;Alshammari et al, 2023). Dampak hemodialisis selain gangguan tidur juga terkait dengan rendahnya kualitas hidup (Lerma et al, 2021;Weigert et al, 2019).…”
Section: Pembahasanunclassified
“…Sleep disorders and fatigue are notably prevalent in patients undergoing HD ( Al Naamani et al, 2021 ) Studies have shown that a significant proportion of HD patients experience sleep-related problems, which include insomnia, restless leg syndrome, and sleep apnea. The prevalence rates of sleep disturbances among HD patients, as revealed by several studies worldwide, range from 40 to 85% ( Al Naamani et al, 2021 ; Alshammari et al, 2023 ) Several factors contribute to the high prevalence of sleep disorders in HD patients. Factors such as stress, dietary restrictions, limited physical activity, and the dialysis schedule can interfere with normal sleep routines and contribute to a sense of fatigue ( Hsouna et al, 2022 ; Abdul Rahim et al, 2023 ; Taheri et al, 2023 ) Poor sleep and fatigue have been linked to worse clinical outcomes in HD patients, including higher morbidity and mortality rates ( Kumar et al, 2010 ) They are associated with an increased risk of cardiovascular events, which are a leading cause of death in this population ( Zhang et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%